2012
DOI: 10.17305/bjbms.2012.2499
|View full text |Cite
|
Sign up to set email alerts
|

TFF1 inhibits proliferation and induces apoptosis of gastric cancer cells in vitro

Abstract: Trefoil Factor Family (TFF) plays an essential role in the intestinal epithelial restitution, but the relationship between TFF1 and gastric cancer (GC) is still unclear. The present study aimed to determine the role of TFF1 in repairing gastric mucosa and in the pathogenesis of GC. The TFF1 expression in different gastric mucosas was measured with immunohistochemistry. Then, siRNA targeting TFF1 or plasmids expressing TFF1 gene were transfected into BGC823 cells, SGC7901 cells and GES-1 cells. The cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In a mouse model, loss of TFF1 promotes gastric dysplasia and adenocarcinoma [3, 8, 9]. Previous studies have shown that TFF1 inhibits growth and promotes apoptosis in gastric cancer cells [11, 12]. However, the mechanism by which TFF1 exerts these effects is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model, loss of TFF1 promotes gastric dysplasia and adenocarcinoma [3, 8, 9]. Previous studies have shown that TFF1 inhibits growth and promotes apoptosis in gastric cancer cells [11, 12]. However, the mechanism by which TFF1 exerts these effects is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Using a Tff1 knockout mouse model, we and others have provided evidence supporting the tumor suppressor function of TFF1 and its anti-inflammatory role in gastric cancer [3, 8, 9]. While there are evidences showing that TFF1 suppresses growth and induces apoptosis in gastric cancer cells [10-12], one study has shown that recombinant TFF1 could have anti-proliferative and anti-apoptotic effects in gastrointestinal cells [13]. The mechanisms by which TFF1 might exert its tumor suppressor functions and promote cell death remain largely unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…From normal gastric to dysplasia and to gastric carcinoma mucosa, the TFF1 expression has a decreasing trend [28]. All normal gastric tissues expressed TFF1, but 53.8% [24]/ 58.3% [72]/ 67.50% [76]/ over 70% [77] of GCs showed reduced TFF1 expression.…”
Section: The Expression Of Tffs In Gastric Cancermentioning
confidence: 99%
“…Genes that could modulate cell growth and death have the potential to be the chemosensitizer of 5‐FU . TFF1 was reported having the function in cell growth and death . And in our functional studies, overexpression of TFF1 in gastric cancer cells enhanced the cytotoxicity of 5‐FU by inhibiting proliferation and promoting apoptosis.…”
Section: Discussionmentioning
confidence: 57%
“…43,44 TFF1 was reported having the function in cell growth and death. [45][46][47] And in our functional studies, overexpression of TFF1 in gastric cancer cells enhanced the cytotoxicity of 5-FU by inhibiting proliferation and promoting apoptosis. NF-jB is the key regulatory signaling molecule responding to multiple stress stimuli, 48 which can be activated by 5-FU and thereby induce the chemoresistance 30,49 through altering the expression of apoptosis-related proteins (such as Bcl-2, Bcl-xl) 50 and cellcycle regulators (such as c-MYC and cyclin D1).…”
Section: Discussionmentioning
confidence: 57%